A Retrospective Case Series of Carbon Fiber Plate Fixation of Ankle Fractures. Issue 3 (June 2018) - Pinter, Zachariah W.; Smith, Kenneth S.; Hudson, Parke W.; Jones, Caleb W.; Hadden, Ryan; Elattar, Osama; Shah, Ashish
Distal fibula fractures represent a common problem in orthopaedics. When fibula fractures require operative fixation, implants are typically made from stainless steel or titanium alloys. Carbon fiber implants have been used elsewhere in orthopaedics for years, and their advantages include a modulus of elasticity similar to that of bone, biocompatibility, increased fatigue strength, and radiolucency. This study hypothesized that carbon fiber plates would provide similar outcomes for ankle fracture fixation as titanium and steel implants. A retrospective chart review was performed of 30 patients who underwent fibular open reduction and internal fixation (ORIF). The main outcomes assessed were postoperative union rate and complication rate. The nonunion or failure rate for carbon fiber plates was 4% (1/24), and the union rate was 96% (23/24). The mean follow-up time was 20 months, and the complication rate was 8% (2/24). Carbon fiber plates are a viable alternative to metal plates in ankle fracture fixation, demonstrating union and complication rates comparable to those of traditional fixation techniques. Their theoretical advantages and similar cost make them an attractive implant choice for ORIF of the fibula. However, further studies are needed for extended follow-up and inclusion of larger patient cohorts. Levels of Evidence: Level IV: Retrospective Case series